Pro sharePoint 2013 business intelligence solutions - Singh, Manpreet; Anandan, Sha Kanjoor; Malik, Sahil; Sistla, Srini; Wright, Steve (Apress Imprint: Apress, 2013)
To get ahead in today's hyper-competitive marketplace, your business has to take advantage of the data you already have and mine that data to give you new insight, metrics, and clues to what drives successful customer interactions.  In Pro SharePoint 2013 Business Intelligence Solutions, you'll learn exactly how to unlock that magic, build business intelligence facilities on SharePoint, and glean insights from data to propel your business to the next level. To understand the various business intelligence offerings in SharePoint 2013, you need to understand the core SQL Server business intelligence concepts, and the first part of the book presents a comprehensive tutorial on those fundamentals. Pro SharePoint 2013 Business Intelligence Solutions then focuses on specific SharePoint business intelligence investments including: Visio Services Excel Services SQL Server Reporting Services Business Connectivity Services Power View and PerformancePoint Services Authors Manpreet Singh, Sha Anandan, Sahil Malik, and Steve Wright walk you through all of this material comprehensively in practical, hands-on format, with plenty of examples to empower you to use these products in your real-life projects. As compelling as SharePoint and SQL Server business intelligence are together, the challenge always has been finding people who understand both SharePoint and SQL Server well enough to deliver such business intelligence solutions. With this book in hand, you become part of that select group. Get your copy of Pro SharePoint 2013 Business Intelligence Solutions today!